ANALISIS NILAI GIZI OTAK-OTAK BANDENG (Chanos sp.) DAN PENINGKATAN KAPASITAS PRODUKSI DENGAN MENGGUNAKAN MESIN PEMISAH DURI: STUDI KASUS UMKM AYAH OLALA, SUKOLILO JAWA TIMUR - Patmawati Patmawati; Wahju Tjahjaningsih; Dwi Yuli Pujiastuti; Maulida Agustina; Ghishella Ayu Rahmawati; Renyta Andini Wahyuningtyas; Zulfan Ibrahimi; Rachmat Fajar Darmawan; Wahyu Saputro (Universitas Mataram, 2023)
Most of the residents in Keputih have a livelihood as milkfish farmers. Milkfish has the potential to be easily contaminated by microorganisms due to its high water content. Another problem related to milkfish is a large number of thorns in the meat, making it difficult to diversify its derivative products, therefore the Meat and Thorn Separator (MT-Separator) is an innovation to separate meat from thorns. Aim of the study is introduced and applied of MT separator to milkfish product from Ayah Olala's SMEs. Community service activities have been carried out from June to October 2022 which took place at the Chemistry Laboratory, Faculty of Fisheries and Maritime Affairs, Airlangga University, Surabaya. Processing of milkfish brains is carried out at Keputih Sukolilo, Surabaya. Community service activities begin with assistance to partners starting from the production process, the storage process, to the packaging process. Particularly emphasis on training the operation of the MT-Separator tool. UMKM Ayah Olala is an UMKM that focuses on processing milkfish brains which are located in Keputih Tegal Gang III No. 2, Sukolilo District, Surabaya City. The implementation of this community service begins with analyzing the problems faced by MSMEs such as business capital, production and managerial. The results of the analysis will then be evaluated to determine the output target to solve the problem. In this activity, partners received assistance from an MT-separator machine. Apart from that, partners also understand how to use the MT separator and the importance of using the tool. Based on the implementation of community service activities, it can be concluded that this activity was successful and provided insight regarding the introduction of product diversification of processed milkfish brains and the introduction of the Meat and Thorn Separator tool. More intensive assistance is needed for Ayah Olala's UMKM starting from the production process, business capital assistance, managerial and operational as well as training in the operation of the MT-Separator tool.